Rapid synthesis of a novel nano-crystalline mesoporous faujasite type metal-organic framework, ZIF-8 catalyst, its detailed characterization, and NaBH4 assisted, enhanced catalytic Rhodamine B degradation. (March 2021) - Chirra, Suman; Wang, Li-Fang; Aggarwal, Himanshu; Tsai, Ming-Fong; Soorian, Siva Sankari; Siliveri, Suresh; Goskula, Srinath; Gujjula, Sripal Reddy; Narayanan, Venkatathri
Graphical abstract: A novel class of mesoporous ZIF-8 materials is synthesized. It is characterized in detail. They are found to have high surface area, nanosize, hollow morphology, Faujasite type structure and synthesized rapidly. Its catalytic activity by NaBH4 assisted Rhodamine B degradation shows an excellent activity. A plausible mechanism is also presented. Highlights: A novel class of mesoporous ZIF-8 materials is synthesized and characterized in detail. They are found to have high surface area, nanosize, hollow morphology, Faujasite type structure, and synthesized rapidly. Its catalytic activity by NaBH4 assisted Rhodamine B degradation shows an excellent activity. A plausible mechanism is also presented. Abstract: In this manuscript, we have reported a strategy for the synthesis and fine control of the crystal size and morphology of a novel mesoporous faujasite type zeolitic imidazolate framework-8 (ZIF-8) nanocrystals in water solution. The synthesized materials are mesoporous faujasite type, highly crystalline, nanometer-sized, and with a high surface area. The materials have been characterized using powder X-ray diffraction (XRD), transmission electron micrograph (TEM), BET-Surface area, and Fourier transform infrared spectroscopic (FT-IR) analysis. The distribution of nanoparticles is observed through DLS spectroscopy. The thermogravimetry/differential thermal analysis reveals that the material is stable even up to 600 °C. Tetrahedral coordination and 4+ oxidation state of Zinc is found through UV–vis and X-ray photoelectron spectroscopies. The NaBH4 assisted rhodamine B degradation at room temperature shows excellent catalytic activity (∼ 95 %) in a short duration (10 min.). A plausible mechanism of degradation on its catalytic activity is also proposed.